Long-term drug survival and causes of discontinuation of subcutaneous abatacept in rheumatoid arthritis: 32-month results from a prospective cohort study (2017)
Background Survival time or time to discontinuation of medication is a surrogate of the long-term impact on the course of disease in real life. It reflects clinical effectiveness in the absence of significant adverse events [1]. Treatment discontinuation can result from loss of efficacy or safety concerns, but prognostic factors for patient retention have not been explored thoroughly despite data for abatacept and other biologics being available from national registries [2]. Objectives To assess drug survival of subcutaneous (SC) abatacept among patients with rheumatoid arthritis (RA) according to treatment background. Methods This was a prospective study in which well-characterized patients with RA (by 1987 ACR criteria) were assessed from April 2014 to December 2016. Each patient was evaluated by a rheumatologist in a single rheumatology outpatient private center in Bogotá, Colombia. Patients were stratified by treatment background: (n=54) biologic-naïve, (n=24) switched from IV to SC abatacept administration, and (n=51) inadequate response to at least 1 biologic disease-modifying antirheumatic drug. The Mantel-Haenszel test was used to test if there were any differences in the survival curves among groups. The test was performed by the survdiff function of the “survival” R package [3]. Results A total of 129 patients were included. Baseline characteristics of patients were as follows: female gender 86%, mean age 52±13 years, median disease duration 10 (IQR 11) years, Rheumatoid Factor positive 94%, Anti-Cyclic Citrullinated Peptide Antibodies 89%, and erosive phenotype 35%. At baseline, mean DAS28 and RAPID3 were 5.4±1.3 and 16.6±6.8, respectively. SC abatacept monotherapy was reported in 27%. Demographics and disease characteristics were similar in all groups, except for baseline DAS28 and RAPID3 in switch group (p<0.0001). According to the Mantel-Haenszel test (Fig.1), there were not significant differences between survival curves (p=0.158). Forty-three patients (33%) discontinued treatment. The most frequent reasons for drug suspension were loss of efficacy in 25%, insurance-related problems (i.e., access to medication/specialist) and adverse drug reactions in 16%. Other causes include lack of efficacy, surgeries (i.e., articular replacement), patient preference, and pregnancy.